Transcriptome analysis of differences in the infection of African swine fever virus (SY-1 strain) in iPAMs and PAMs - Mao, Haiying; Cheng, Chuxing; Wang, Yong; Zhou, Wenhui; Zhang, Ke; Wang, Yongqi; Wang, Lihao; Song, Zhenrui; Sun, Xiaomei; Zhang, Yuanfeng; Hu, Xiaotong; Zhang, Yumei; et al. (Frontiers in Immunology, 2025)
African swine fever (ASF) is a highly contagious hemorrhagic disease caused by African swine fever virus (ASFV), which has inflicted devastating impacts on the global swine industry. Currently, no commercially available vaccines exist. A major obstacle in ASF research of mechanistic exploration and vaccine studies is the virus’s strict tropism for primary cells like porcine alveolar macrophages (PAMs), while exhibiting poor susceptibility to most immortalized cell lines. This study compared the replication and host response of the ASFV SY-1 strain in PAMs versus immortalized porcine macrophage cell lines (iPAMs) using qPCR, western blot, and early infection transcriptome data. Results revealed that the SY-1 strain replicates only minimally in iPAMs, with significantly lower replication capacity than in PAMs. Transcriptomic data demonstrated divergent host responses: iPAMs predominantly involved in in the regulation of lipid metabolism and response to oxidative stress, whereas PAMs preferentially activate cytokine signaling and immune responses. Furthermore, Functional validation indicated JPH4 and CYP1A1 (selected from differentially expressed genes list) as potential host factors influencing viral replication. This study delineates early host–virus dynamics in ASFV susceptible cells (PAMs) and restricted replicating cells (iPAMs), which not only provides an insight into the replication of ASFV but also improved rational design of antiviral strategies in ASF research.